DNA Damage-Induced G(1) Arrest in Hematopoietic Cells Is Overridden following Phosphatidylinositol 3-Kinase-Dependent Activation of Cyclin-Dependent Kinase 2 - Eapen, Alex K. (American Society for Microbiology, 2001)
Exposure of hematopoietic cells to DNA-damaging agents induces p53-independent cell cycle arrest at a G(1) checkpoint. Previously, we have shown that this growth arrest can be overridden by cytokine growth factors, such as erythropoietin or interleukin-3, through activation of a phosphatidylinositol 3-kinase (PI 3-kinase)/Akt-dependent signaling pathway. Here, we show that γ-irradiated murine myeloid 32D cells arrest in G(1) with active cyclin D–cyclin-dependent kinase 4 (Cdk4) but with inactive cyclin E-Cdk2 kinases. The arrest was associated with elevated levels of the Cdk inhibitors p21(Cip1) and p27(Kip1), yet neither was associated with Cdk2. Instead, irradiation-induced inhibition of cyclin E-Cdk2 correlated with absence of the activating threonine-160 phosphorylation on Cdk2. Cytokine treatment of irradiated cells induced Cdk2 phosphorylation and activation, and cells entered into S phase despite sustained high-level expression of p21 and p27. Notably, the PI 3-kinase inhibitor, LY294002, completely blocked cytokine-induced Cdk2 activation and cell growth in irradiated 32D cells but not in nonirradiated cells. Together, these findings demonstrate a novel mechanism underlying the DNA damage-induced G(1) arrest of hematopoietic cells, that is, inhibition of Cdk2 phosphorylation and activation. These observations link PI 3-kinase signaling pathways with the regulation of Cdk2 activity.